In Vitro Evaluation of the Aberdeen Knot for Continuous Suture Patterns with Large Gauge Suture. Issue 7 (8th September 2016) - Gillen, Alex M.; Munsterman, Amelia S.; Farag, Ramsis; Coleridge, Matthew O. D.; Reid Hanson, R.
Abstract : Objective: To evaluate the strength, size, and holding capacity of the Aberdeen knot compared to surgeon's and square knots using large gauge suture. Study Design: In vitro mechanical study. Study Population: Knotted suture. Methods: Aberdeen, surgeon's, and square knots were tested using 2 and 3 USP polyglactin 910 and 2 USP polydioxanone under linear tension on a universal testing machine. Mode of failure and knot holding capacity (KHC) were recorded and relative knot security (RKS) was calculated as a percentage of KHC. Knot volume and weight were quantified by a digital micrometer and balance, respectively. Strength between number of throws, suture, suture size, and knot type were compared by ANOVA and post hoc testing. P ≤.05 was considered significant. Results: Aberdeen knots had higher KHC and RKS than surgeon's or square knots for all suture types and number of throws ( P <.001). For all suture materials, none of the Aberdeen knots unraveled, but a portion of square and surgeon's knots with <7 throws did unravel ( P =.101). Aberdeen knots had a smaller volume and weight than both surgeon's and square knots with equal numbers of throws ( P <.001). The knot with the combined highest RKS and smallest size and weight was an Aberdeen knot with 4 throws using 3 USP polyglactin 910. Conclusion: The Aberdeen knots were stronger, more secure, and smaller than surgeon's and square knots for ending a continuous suture pattern. Clinically, the Aberdeen knot may be a useful alternative for completion of continuous patterns using large gauge suture, without sacrificing knot integrity.